Partisipasi Masyarakat Dalam Pembentukan Undang-Undang - Tuhumena, Callychya Juanitha Raisha; Pietersz, Jemmy Jefry; Sedubun, Victor Juzuf (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Community participation is a stage that engages the community in participating in the process of forming laws and regulations. Purposes of the Research: The purpose of this writing is to determine the consequences of the formation of laws that do not involve public participation.Methods of the Research: The research method used is normative legal research. With the approach used, namely the statute approach, and the conceptual approach.Results of the Research: The results of this study indicate that community participation is a stage that provides opportunities for the community, in reports, invitations in accordance with the provisions of the law. Community participation implies that community participation contains legal norms that are imperative. How successful is the community's successful procedure that must be carried out in the ordering of statutory regulations.